Late onset of a persistent, deep stromal and endothelial scarring after corneal collagen crosslinking for keratoconus: A case report. Issue 6 (November 2022) - Fuchs, Barbara; Wendelstein, Jascha; Mariacher, Siegfried; Tetz, Kristin; Bolz, Matthias; Fischinger, Isaak
Introduction: To report a late onset, deep stromal and endothelial corneal scar in a keratoconus patient after corneal collagen cross-linking (CXL). Case description: Observational case report. A 29-year-old man with bilateral keratoconus received an accelerated (A-CXL 10*9) epithelium-off CXL procedure in the left eye. 6-months postoperatively, a 2.2 × 1.2 mm inferocentral corneal scar was detected, which was located in the posterior stroma ranging from approximately 350 µm until the endothelium, therefore was situated below the demarcation line. A topical corticosteroid treatment did not influence the magnitude or configuration of the scar. Visual acuity was never affected, which includes the examination 12 months postoperatively. Conclusions: We report a case of a late onset deep stromal and endothelial corneal scar 6 months after accelerated CXL as postoperative complication without affecting visual acuity.